Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3892/ijo.2015.3058
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Livin inhibits tumorigenesis and metastasis via VEGF and MMPs pathway in lung cancer

Abstract: Abstract. Livin, an inhibitor of apoptosis protein (IAP), is overexpressed in various cancers and decreases tumor sensitivity to chemotherapy and radiotherapy. However, the effect of Livin on lung adenocarcinoma metastasis and the specific mechanism involved remain unclear. RNAi technology was used to stably silence Livin in A549 cells in the present study. The effect of Livin on tumor growth and invasion was investigated in lung cancer cells in vitro and animal models were established to determine the anti-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…(Salajegheh et al 2011, Das & Wakelee 2012, Rajabi et al 2012. In this pathway of tumour angiogenesis and in the downstream of VEGF, many proteins such as MMP2 and MMP9 have been reported to be involved in the enhancement and expansion of neo-angiogenesis process in different malignant lesions (Turner et al 2003, Lin et al 2015, Mahecha & Wang 2017. Interaction of VEGF and MMPs have been reported in lung cancer, endometrial cancer and breast cancer (Radisky & Radisky 2010, Lin et al 2015, Mahecha & Wang 2017.…”
Section: Discussionmentioning
confidence: 99%
“…(Salajegheh et al 2011, Das & Wakelee 2012, Rajabi et al 2012. In this pathway of tumour angiogenesis and in the downstream of VEGF, many proteins such as MMP2 and MMP9 have been reported to be involved in the enhancement and expansion of neo-angiogenesis process in different malignant lesions (Turner et al 2003, Lin et al 2015, Mahecha & Wang 2017. Interaction of VEGF and MMPs have been reported in lung cancer, endometrial cancer and breast cancer (Radisky & Radisky 2010, Lin et al 2015, Mahecha & Wang 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-apoptotic potential of Livin and its preferential expression in osteosarcoma, at very low or undetectable levels in the corresponding normal tissue, suggest that the manipulation of Livin expression could represent a novel and tumor-specific molecular target for cancer therapy (23). Zhuang et al (24) demonstrated that long-term silencing of Livin expression inhibited the proliferation of Livin-expressing non small-cell lung cancer cells and increased the chemosensitivity of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have linked Livin to metastasis in multiple solid tumors, such as lung cancer, 19 breast cancer, 20 , 21 gastric cancer, 17 and laryngohypopharyngeal cancer. 16 In CRC, ectopic overexpression of Livin correlates with tumor metastasis and implies poor prognosis.…”
Section: Discussionmentioning
confidence: 99%